2012
DOI: 10.2478/s11532-012-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Visible light photocatalytic activity of TiO2 deposited on activated carbon

Abstract: Abstract:© Versita Sp. z o.o. Four photocatalyst samples, prepared from beech sawdust, were synthesized by an original method, combining pyrolysis and impregnation -two of them: TiO 2 + activated carbon and other two -only activated carbon. The pyrolysis process has been carried out at two different temperatures -680°C and 830°C. The prepared samples were characterized by a series of methods -XRD, BET, SEM and DTA/TG. The most important result was achieving visible light photocatalytic activity with an azo dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In comparison, the photocatalysis is a promising advanced oxidation process, which usually uses heterogeneous titanium dioxide (TiO 2 ) as a photocatalyst to degrade the contaminants by the decomposition and oxidation processes on its surface [13][14][15]. However, there are some disadvantages of TiO 2 used in advanced oxidation process as TiO 2 powder is easy to agglomerate, with poor adsorption capacity, and is difficult to be separated and recycled from the solution [5,16,17]. For the purpose of overcoming the drawbacks of these two approaches, the combination of adsorption and photocatalytic processes was previously proved to be a very promising technology for the treatment of wastewater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the photocatalysis is a promising advanced oxidation process, which usually uses heterogeneous titanium dioxide (TiO 2 ) as a photocatalyst to degrade the contaminants by the decomposition and oxidation processes on its surface [13][14][15]. However, there are some disadvantages of TiO 2 used in advanced oxidation process as TiO 2 powder is easy to agglomerate, with poor adsorption capacity, and is difficult to be separated and recycled from the solution [5,16,17]. For the purpose of overcoming the drawbacks of these two approaches, the combination of adsorption and photocatalytic processes was previously proved to be a very promising technology for the treatment of wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Jamil et al [30] synthesized photocatalyst by AC impregnated with TiO 2 for the removal of methyl orange from water, and the synergistic effects of adsorption and photocatalytic activity in TiO 2 / AC for the degradation of the methyl orange have been found. Eliyas et al [17] prepared a TiO 2 /AC composite by an original method combining impregnation and physicochemical pyrolysis, and the photocatalytic decomposition of an azo dye pollutant under visible light illumination and ultraviolet (UV) light irradiation was studied. Zhang et al and He et al [6,31] investigated the degradation of methyl orange and Rhodamine B (RhB) by microwave-induced photocatalytic technology using TiO 2 /AC composites.…”
Section: Introductionmentioning
confidence: 99%
“…Their use has been often prohibited mainly due to their relatively high cost, low selectivity and regeneration problems; they can be regenerated by thermal desorption of the adsorbed substances or by liquid phase extraction in the case of soluble adsorbed species, although the former method is not very environmentfriendly and leads to partial mass loss of the adsorbent [12,16,24,32,48,52,54,63]. The microporous nature of the majority of porous activated carbons is well suited to many applications, including molecular sieving, sorption and catalytic reactions of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that an AC-TiO 2 mixture has a positive effect on photocatalytic activity in the degradation of organic pollutants. In other words, AC, due to its high adsorption capability, can aid in enriching the organic pollutant around the TiO 2 nano-particles, increasing the pollution transfer process and, hence, promoting photocatalytic efficiency [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%